2009
DOI: 10.1186/1471-2458-9-261
|View full text |Cite
|
Sign up to set email alerts
|

A free weekly iron-folic acid supplementation and regular deworming program is associated with improved hemoglobin and iron status indicators in Vietnamese women

Abstract: Background: Anemia due to iron deficiency is recognized as one of the major nutritional deficiencies in women and children in developing countries. Daily iron supplementation for pregnant women is recommended in many countries although there are few reports of these programs working efficiently or effectively. Weekly iron-folic acid supplementation (WIFS) and regular deworming treatment is recommended for non-pregnant women living in areas with high rates of anemia. Following a baseline survey to assess the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 32 publications
3
57
0
2
Order By: Relevance
“…Casey et al (40) 2009 Vietnam Weekly distribution of universal IFA supplementation and deworming medication for WRA through village health workers and integration into existing health services…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 1 more Smart Citation
“…Casey et al (40) 2009 Vietnam Weekly distribution of universal IFA supplementation and deworming medication for WRA through village health workers and integration into existing health services…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
“…Impact of community-based distribution of iron-folic acid supplementation: coverage and reductions in maternal anaemia Targeting pregnant women and WRA through community settings demonstrated increased accessibility, high compliance, and reductions in anaemia in thirteen studies (20,23,24,25,28,30,(34)(35)(36)(37)40,42) . Nicaragua increased IFA supplementation coverage among pregnant women to over 80 % and experienced a substantial drop in anaemia prevalence through use of community-based distributors who provided counselling and follow-up to pregnant women (39) .…”
Section: Barriers To Successful Roll-out Of Community-based Distributmentioning
confidence: 99%
“…More recently, Meenakshi et al (2010) concluded that overall, biofortification can make a significant impact on reducing the burden of micronutrient deficiencies in the developing world in a highly cost-effective manner; however, the impacts differ depending on the combination of crop, micronutrient and country, and the major reasons underlying these differences are identified to inform policy. In the past, food fortification, diet diversification, and nutrient supplementation have been most frequently used as public health interventions to reduce micronutrient-induced morbidity and mortality worldwide (Suharno et al 1993;Haider et al 2003;Brown et al 2007;Wienecke and Gruenwald 2007;Casey et al 2010;Eneroth et al 2010). However, these approaches have had only limited success and could not by themselves attain sufficiently millennium development goals mainly because such interventions require infrastructure, continuous flow of resources, purchasing power, or access to markets and health care systems to their success, often not available to people living in remote areas (Underwood 1999;Imhoff-Kunsch et al 2007;Ssemakula and Pfeiffer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…6 Program di Vietnam dinilai berhasil menurunkan prevalensi anemia dikarenakan program suplementasi ditambahkan dengan pemberian intervensi obat cacing serta diikuti edukasi kepada sasaran. 7 Penelitian yang dilakukan Susanti di Kabupaten Tasikmalaya dengan program pemberian TTD secara mingguan dan 10 tablet selama menstruasi mengalami peningkatan kadar Hb sebanyak 0.48±1.04 g/dl. 8 Program serupa yang dilakukan pada wanita usia subur di Vietnam mengalami peningkatan kadar Hb selama 3 bulan intervensi yakni rata-rata meningkat sebesar 9.6 g/dl.…”
Section: Hasilunclassified
“…8 Program serupa yang dilakukan pada wanita usia subur di Vietnam mengalami peningkatan kadar Hb selama 3 bulan intervensi yakni rata-rata meningkat sebesar 9.6 g/dl. 7 Berbeda halnya dengan program suplementasi besi yang dilakukan di Kota Bekasi pada siswi SMP dan SMA, tidak terjadi peningkatan kadar Hb setelah diberikan suplementasi. 3 Status gizi merupakan salah satu faktor untuk menetapkan diagnosis anemia seseorang.…”
Section: Hasilunclassified